ANALYSIS OF CRIMINAL LIABILITY FOR PERPETRATORS OF PHYSICAL VIOLENCE IN DOMESTIC RELATIONSHIPS - Tami Rusli; Roy Chandrito Sagala (RADJA PUBLIKA, 2026)
Physical violence within the domestic sphere remains one of the most prevalent forms of criminal offense, causing significant adverse impacts on victims as well as on family life. This study aims to analyze the factors contributing to the occurrence of physical domestic violence and to examine the criminal liability of perpetrators based on Decision Number 329/Pid.Sus/2025/PN.Gns. This research employed both normative juridical and empirical juridical approaches. The data were collected through library research and field research, including interviews with investigators from the Central Lampung Regional Police, public prosecutors at the Central Lampung District Attorney’s Office, and judges of the Gunung Sugih District Court. The data were analyzed using a qualitative juridical method.The results indicate that physical domestic violence is influenced by psychological factors, the family environment, patriarchal culture, as well as social and economic factors that encourage perpetrators to commit acts of violence against victims. The criminal liability of the perpetrator is established based on the fulfillment of the elements of the criminal offense as stipulated in Article 44 paragraph (1) of Law Number 23 of 2004 on the Elimination of Domestic Violence. Based on the facts revealed during the trial, the defendant was legally and convincingly proven guilty of committing physical violence against his wife and was therefore sentenced to imprisonment in accordance with the court's decision. The judgment reflects the application of the principle of criminal liability, which is based on the existence of the perpetrator’s culpability and the fulfillment of lawful evidence in accordance with the Indonesian Code of Criminal Procedure.